2005
DOI: 10.1523/jneurosci.2038-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Antidiabetic Pioglitazone Protects from Neurodegeneration and Amyotrophic Lateral Sclerosis-Like Symptoms in Superoxide Dismutase-G93A Transgenic Mice

Abstract: Amyotrophic lateral sclerosis (ALS) represents a fatal neurodegenerative disorder characterized by progressive death of the upper and lower motor neurons. Because accompanying inflammation may interact with and promote neurodegeneration, anti-inflammatory treatment strategies are being evaluated. Because peroxisome proliferator-activated receptor ␥ (PPAR␥) agonists act as potent antiinflammatory drugs, we tested whether superoxide dismutase (SOD1)-G93A transgenic mice, a mouse model of ALS, benefit from oral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
152
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(162 citation statements)
references
References 53 publications
(60 reference statements)
8
152
1
1
Order By: Relevance
“…Second, A2a receptor antagonists protect purified motor neurons from insult indicating the lack of necessity of nonmotor neurons and glial cells in the biological effect. Thus, although ALS is increasingly being viewed a disorder that involves the participation of multiple cell types (i.e., astrocytes, muscle, microglia), the present results highlight motor neuron-specific processes (Clem-ent et al, 2003;Dupuis et al, 2003Dupuis et al, , 2004Barbeito et al, 2004;Pehar et al, 2004;Cassina et al, 2005;Schutz et al, 2005).…”
Section: Discussionmentioning
confidence: 55%
“…Second, A2a receptor antagonists protect purified motor neurons from insult indicating the lack of necessity of nonmotor neurons and glial cells in the biological effect. Thus, although ALS is increasingly being viewed a disorder that involves the participation of multiple cell types (i.e., astrocytes, muscle, microglia), the present results highlight motor neuron-specific processes (Clem-ent et al, 2003;Dupuis et al, 2003Dupuis et al, , 2004Barbeito et al, 2004;Pehar et al, 2004;Cassina et al, 2005;Schutz et al, 2005).…”
Section: Discussionmentioning
confidence: 55%
“…First, the possibility cannot be ruled out that the brain utilises more of a fuel other than glucose, such as lactate of peripheral origin [37]. Second, pioglitazone treatment may be protective by limiting the highest rates of regional glucose oxidative metabolism and the concomitant oxidative stress [14,32,38,39], in association with the benefits derived from the attenuation of inflammation [5]. Finally, pioglitazone can induce the expression of proteins related to the stress response [40] and mitochondrial membrane hyperpolarisation that can safeguard the cells against an excessive metabolic rate [9].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that thiazolidinediones are potent inhibitors of inflammation [3][4][5] has prompted several clinical trials testing the effects of thiazolidinediones in neurological diseases such as Alzheimer's disease and multiple sclerosis, in which inflammation contributes to pathogenesis [6]. The antiinflammatory properties of pioglitazone in the brain have also been shown in murine models of acute [7] and chronic [8] inflammation, when this thiazolidinedione was administered to the animals orally.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PPAR␥ agonists induce mt biogenesis and oxidative metabolism, 15,16 and protect against neurodegeneration and amyotrophic lateral sclerosis by increasing mt function. 17,18 Our previous study showed that Aldo-induced renal proximal tubular epithelial cell injury was mediated by mt reactive oxygen species (ROS). 6 We postulated that the same mediator (ie, mt ROS) may contribute to Aldo-induced podocyte injury and may serve as a therapeutic target of PPAR␥ agonists in renal diseases.…”
mentioning
confidence: 99%